Designing a NovelTwo-tier authentication algorithm for web service architecture - Milton Joe, M.; Ramakrishnan, B.; Das, Resul (Universiti Teknikal Malaysia Melaka, 2016)
Web pages are secured by one-tier security constraints based on username and password. This one-tier security module is the only way to protect the web pages from hackers. However, the one-tier security constraints on web service architecture have several flaws. It can be hacked from outside without notifying the authorised user. Further, hackers can easily obtain the username and password, which is entered on the web pages to login for further actions. When the system is connected to the internet, the system can be hacked to get the username and password that can be done by monitoring user's keystroke from a remote location. Considering the credentials of one-tier security constraints are being hacked, this paper analyses these flaws and modelled two-tier security constraints to secure the web service. In the proposed architecture pattern, recognition mechanism is used to authenticate the user. The pattern recognition architecture displays at dynamic locations for each refresh of the web page, which prevents the proposed two-tier architecture from being hacked as well as guessing attack.
Keywords: Authentication; Hacking; Internet; One-Tier; Pattern recognition; QoS; Security; Two-Tier; Web